The Theology of the Cross by Jürgen Moltmann - Cardoso Bertoldo, Fernando (Vox Scripturae - Revista Teológica Internacional, 2025)
For Jürgen Moltmann, the crucifixion of Christ represents the abandonment of God to human suffering. Understanding this abandonment would lead individuals to free themselves from religious distortions, in view of this solidarity of God with human pain. Thus, we start from the assumption that Christ is God and man, demonstrated in his humanity and therefore precisely by its manifestation in our lives, we realize that God is not an apathetic figure and insensible to human restlessness. We understand that the revelation of God in Christ is fundamentally the renunciation of idols and power. Consequently, God would protect us by giving up our suffering for the sake of humanity. Jesus is simultaneously understood as the God who empties himself of power, who takes the path of the cross in the deepest helplessness, and also as the man who portrays authentic humanity in a helpless helplessness.
Keywords: Jürgen Moltmann; Theology of the Cross; Theology of Hope; Divine suffering